Here are some very important things we have discovered so far:

Putting these understandings together we find that
Here are two examples showing that each subtraction problem has a related addition problem that gives the exact same answer.
5 – (8) = 13  
5 + 8 = 13 
5 – 2 = 3  
5 + (2) = 3 
Let's practice a little:
Change the subtraction expression into an addition expression. Then simplify. 

(4) – (+6) 
(4) – (+6) will result in the same answer as (4) + (6). (4) – (+6) = (4) + (6) = 10 
(7) – (9) 
(7) – (9) will result in the same answer as (7) + (+9) (7) – (9) = (7) + (+9) = +2 
(+3) – (+5) 
(+3) – (+5) will result in the same answer as (+3) + (5) (+3) – (+5) = (+3) + (5) = 2 
(+8) – (2) 
(+8) – (2) will result in the same answer as (+8) + (+2) (+8) – (2) = (+8) + (+2) = +10 
By looking at the four examples above, we can see a pattern that occurs in each of the examples:
In fact, the rule for subtracting positives and negatives is:
To subtract two integers: 
Question 1 Write the following expression using addition. Then simplify. (+8) – (5) 
[show answer] 
Question 2 Write the following expression using addition. Then simplify. (3) – (4) 
[show answer] 
Question 3 Write the following expression using addition. Then simplify. (6) – (+7) 
[show answer] 